A new species of Petunia (Solanaceae) from Corrientes, Argentina - Greppi, Julián Alejandro; Hagiwara, Juan Carlos; Stehmann, João Renato (Phytotaxa, 2019)
We describe and illustrate a new species of Petunia, P. correntina, from southwestern Corrientes, Argentina, in southern South America. The species has funnel-form corolla with whitish-green tube and purple lobes, apex of longer filaments nearly straight, apex of medium filaments curved laterally and opposite each other, connivent anthers, bluish pollen, stigma located between anthers of the large and medium stamens and inflexed pedicels in fruiting stage. This suit of characters is unique into the genus. Few populations are known, inhabiting sandy soils of the Paraná basin. A key to the Argentinian species of Petunia with purple corolla is given.